EXPLORING STUDENTS' DIFFICULTIES IN SPEAKING SKILLS AT KHAIRUN UNIVERSITY - Anwar, Indry Widyasti; Ismail, Putri Nabila; Bahara, Susana R. (Jurnal Bilingual, 2024)
This study aims to investigate the factors contributing to the challenges encountered by students in class A, semester 3 of the English Education Study Program at Khairun University when speaking English, as well as the reasons behind these difficulties. The study involved 36 students as its subjects and utilized qualitative research methods, with data being collected through questionnaires and interviews. The questionnaire used was adapted from Gustina (2021), and six factors of difficulty were discussed, namely linguistic obstacles, speech processing, academic and conversational English skills, negative effects, access to speaking opportunities, and fluency. The findings of this study indicate that students struggle with speaking English due to challenges such as insufficient vocabulary, poor grasp of grammar, lack of confidence, and motivation. The primary factor contributing to the difficulty in speaking English is the linguistic barrier.